The Nature of War - Otto, W (Scientia Militaria - South African Journal of Military Studies, 2011)
Ever since the advent of recorded history man has engaged in warfare - so much so that it sometimes seems that prevailing conditions of mankind, were merely interrupted from time to time by brief episodes of peace. This book records this phenomenon cyclically - from peace to outbreak, through campaigns, battles, sieges, invasions, retreats, surrenders, aftermath and return to peace.